Energy use analysis of the variable refrigerant flow (VRF) system versus the multi - split unit using TRNSYS - Yau, Yat Huang; ‘Amir, M. (Springer Verlag (Germany), 2020)
The usage of air - conditioning in the residential and commercial buildings is becoming necessary because of the enormous demand for thermal comfort and healthy indoor environment. In achieving human thermal comfort and healthy indoor environment in a large building, there are many types of air conditioning systems that can be used, including the multi - split type unit and the variable refrigerant flow (VRF) system. The present research analyses the annual energy use of the existing ACMV system (multi - split type ceiling cassette unit) installed in the examined building, which located in the tropical area and compares it with a VRF system. The TRNSYS software is used to simulate both of these systems in accordance with the existing building’s characteristics and its operation. The existing building’s characteristics and its operation are obtained by conducting the site survey and field measurements in the building. In the current paper, the bin method is used to estimate the annual energy consumption for these systems. Based on the simulation results, the existing ACMV system consumes more energy in comparison to the VRF system by 13.62%. In addition, the annual operating cost of these systems has shown that the VRF system has a lower annual operating cost in comparison to the existing ACMV system by 13.63%. Besides that, the VRF system can accommodate an estimated payback period of around 6.6 years and an internal rate of return of 12.75%. The result has suggested that the VRF system has a great potential in energy savings and could reduce the electricity consumption in a large building significantly. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.